UNEXPECTED CAREGIVING: LIFE AFTER A COVID-19 INTENSIVE CARE UNIT HOSPITALIZATION. (20th December 2022) - Robinson-Lane, Sheria; Johnson, Florence; Leggett, Amanda; Carmichael, Alicia; Leonard, Natalie; Gonzalez, Richard
Abstract: The coronavirus pandemic has led to an exceptional number of critical care hospitalizations followed by extended recovery periods that necessitate familial support. Using a qualitative descriptive approach, this study aimed to examine the strategies used by families to adjust to the caregiving role. Semi-structured interviews of patients who had been recently discharged from the Intensive Care Unit (ICU) (n=16) along with their family caregivers (n=16) were thematically analyzed. Three major themes were identified that highlight how family caregivers adapt to the caregiving role following an ICU COVID-19 related hospitalization including 1) engaging the support of family and friends, 2) shifting responsibilities to accommodate caregiving, and 3) managing one's emotions. Additional themes more specifically related to managing COVID-19 care included: 1) managing infection control, 2) care recipient's need for independence, and 3) managing support services. Flexibility and sufficient support allowed family caregivers to manage their new caregiving role and function optimally.